Minat Baca Mahasiswa Terhadap Buku Fisik dan Buku Elektronik - Krisniady, Cecep Tedy (Forum Perpustakaan Perguruan Tinggi Indonesia, 2022)
As time goes by, traditional printed books have shifted to electronic formats. This research aims to determine the level of reading engagement of Hermina Manggala Husada Nursing Academy students regarding physical and electronic books. The quantitative and qualitative approach involves filling out questionnaires and interviews. The population studied were students registered at Hermina Manggala Husada Nursing Academy, especially at levels one, two, and three. Research findings show that Hermina Manggala Husada Nursing Academy students prefer to read books, either in physical or electronic format, without thinking about the medium. Based on the responses obtained from the questionnaire, it was determined that 35 people, equivalent to 50% of the sample size (70), expressed a greater inclination towards reading physical books compared to electronic books. On the other hand, a small number of respondents, including four people or 5.7% of the sample, disagreed with the statement that they prefer physical books over electronic books. Regarding the accessibility of physical and electronic books, the individual stated that obtaining both formats is very easy. Based on calculations, 38 people, including 54.3% of the 70 samples, agreed with easy access to electronic and physical books. The product of 4.3% and 70 equals three individuals with different viewpoints. Physical and electronic books continue to captivate readers because of the inherent value of the information they carry. Electronic and print media are modes of communication and information dissemination. Preserving and cultivating a love of reading is very important.